2000
DOI: 10.1161/01.res.87.10.929
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Optical Mapping of the Right Bundle Branch in Connexin40 Knockout Mice Reveals Slow Conduction in the Specialized Conduction System

Abstract: Abstract-Connexin40 (Cx40) is a major gap junction protein that is expressed in the His-Purkinje system and thought to be a critical determinant of cell-to-cell communication and conduction of electrical impulses. Video maps of the ventricular epicardium and the proximal segment of the right bundle branch (RBB) were obtained using a high-speed CCD camera while simultaneously recording volume-conducted ECGs. In Cx40 -/-mice, the PR interval was prolonged (47.4Ϯ1.4 in wild-type [WT] [nϭ6] and 57.5Ϯ2.8 in Cx40-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
120
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 54 publications
15
120
2
Order By: Relevance
“…Whereas studies in anesthetized mice have revealed a marked prolongation in the duration of the P wave, 27,36,40,41 prolongation of the P wave has been reported to be minor or absent in conscious animals. 42,43 Direct measurements with optical mapping revealed a highly abnormal pattern of electrical excitation and propagation in the right atria of adult Cx40 Ϫ/Ϫ mice, 43 attributable to circumscribed intraatrial conduction slowing in …”
Section: Discussionmentioning
confidence: 99%
“…Whereas studies in anesthetized mice have revealed a marked prolongation in the duration of the P wave, 27,36,40,41 prolongation of the P wave has been reported to be minor or absent in conscious animals. 42,43 Direct measurements with optical mapping revealed a highly abnormal pattern of electrical excitation and propagation in the right atria of adult Cx40 Ϫ/Ϫ mice, 43 attributable to circumscribed intraatrial conduction slowing in …”
Section: Discussionmentioning
confidence: 99%
“…35 Thus, functional effects of changed Cx expression may be difficult to predict directly, particularly when alterations in multiple isoforms are observed. On the other hand, Cx40 knockout clearly slows His-Purkinje system conduction in the mouse, 36 and decreases in Cx43 expression slow ventricular conduction. 37 There is evidence that colocalization of Cx40 and Cx43 in PFs may be functionally important.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The collected data fall into 4 different categories based on the mode in which they were reported in the literature for each of the 3 parameters (ie, PR, HR, and BM): (1) measurements from single animals, (2) multiple animal measurements reported as mean values without SD, (3) multiple animal measurements reported as means with SDs, and (4) values reported as ranges without means or SDs. For convenience, the allometric equation YϭY 0 · BM b can be transformed into a logarithmic form, lnYϭlnY 0 ϩb · lnBM, which describes a straight line of the form yϭinterceptϩbx.…”
Section: Data Collection and Analysismentioning
confidence: 99%